Diabetes triggers the loss of tooth structure associated to radiographical and histological dental changes and its evolution to progressive pulp and periapical lesions in rats - Claudino, Marcela; Nunes, Isabela Sousa; Gennaro, Gabriela; Cestari, Tania Mary; Spadella, César Tadeu [UNESP]; Garlet, Gustavo Pompermaier; Assis, Gerson Francisco de (Elsevier B. V., 2015)
The aim of this study was to evaluate the putative influence of diabetes without metabolic control in the loss of tooth structure as well as histological changes in dentin and pulp tissue in rats. Diabetes was induced in Wistar rats (n=25) by intravenous administration of alloxan (42mg/kg). Diabetic and non-diabetic control rats were evaluated at 1, 3, 6, 9 and 12 months of follow-up. In order to evaluate the presence and progression of dental caries and periapical lesions, hemimandibles were removed and submitted to radiographical, histological, and morphometrical procedures. Dental caries were detected after radiographical and histological evaluations in diabetic group from the third month of diabetes onset, increasing gradually in frequency and severity in periods. Diabetic rats dental pulps also presented significant reduction in volume density of collagen fibers and fibroblasts at third month, parallel with a trend towards the increase in inflammatory cells volume density. Diabetic rats presented a generalized pulp tissue necrosis after 6 months of diabetes induction. Moreover, periapical lesions were not detected in control group, while these lesions were observed in all rats after 3, 6, 9, and 12 months of diabetes induction. Uncontrolled diabetes seems to trigger the loss of tooth structure, associated to histological dental changes and mediates its evolution to progressive severe pulp and periapical lesions in rats. Therefore, diabetes may be considered a very important risk factor regarding alterations in dental pulp, development of dental caries, and periapical lesions.
Keywords: Alloxan; Dental caries; Dental pulp; Diabetes mellitus; Rats